NASA Microgravity Solidification Experiments for the International Space Station - McElderry, Justin; Phillips, Tristan; Hardyman, Micah; Ragan, James; Rameshbabu, Rahul (Proceedings of the Wisconsin Space Conference, 2019)
MMaJIC (Microgravity Materials Joining Investigation Chamber) is a modular experiment environment for performing materials science investigations. MMaJIC provides a controlled and sealed test environment for a wide variety of soldering and brazing experiment to examine porosity in microgravity. MMaJIC’s modular cartridge design includes a tray for housing the solder experiments demonstrates simplicity to astronauts. SoLIDD (Solid Liquid Interface Directional Device) is a device that is used to test samples for directional solidification experiments. Directional solidification is the method of controlling the microstructure of materials. Solidification is useful for creating higher strength materials for space casting. SoLIDD has the capability for varying temperature gradient and growth velocity. These quantities utilize heaters, coolers, and a directional drive unit. Two high-resolution cameras capture high-resolution video of both experiments and thermocouples record live-stream temperature data. Both devices are approved by NASA Headquarters to be contracted to the International Space Station for further investigation.